ABOUT OPERATION OF POWER TRANSFORMERS - A. A. Gonchar (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Characteristics of power transformers have been considered in the paper. It has been shown that maximum value of transformer efficiency does nor correspond to minimum of its power losses. It is recommended to apply transformers in the areas which are beyond loading factor, corresponding to maximum efficiency.